Restitusi Sebagai Wujud Pemenuhan Hak Korban Tindak Pidana Kekerasan Seksual di Indonesia - Maria Novita Apriyani (Jurnal Risalah Hukum, 2021)
Sexual violence cases are rife in our environment. The current Criminal Code (KUHP) only focuses on punishing the perpetrators and has not considered the best legal remedies for victims of sexual violence. This study aims to determine the implementation of restitution to fulfill the rights of victims of sexual violence crime. This research is an empirical study by looking at the implementation of restitution of the laws and regulations run by the Witness and Victim Protection Agency (LPSK). The results of this study indicate that the victim's application for restitution can be submitted through the LPSK along with the criminal process, even starting from the beginning of the investigation. The challenges faced by LPSK as an institution that facilitates restit ution for victims of sexual violence include. The a limited number of psychologistsin some areas. Lack of support from the community. The fulfillment of restitution rights that have not been implemented effectively. The obstacle experienced by law enforce ment officers in implementing restitution for victims of sexual violence is that there has not been a coercive effort for perpetrators of sexual violence to pay restitution decided in court. Keywords : Implementation; Restitution; Victim; Sexual Violence